8x2+6x-2
I think! because 8,6, and 2 are all divisible by 2
and 3. Factor the quadratic
2(4x-1)(x+1)
The second one !!!
I’m pretty sure
Answer:
18
Step-by-step explanation:
i just took the test and got a 100% :)
Answer:
-20
Step-by-step explanation:
x(-y+z) [Switch in the values]
=5(-5+1) [Use distributive property and multiply]
=(-25)+5 [do the basic math]
=(-20) [final answer]
Answer:
f^-1(x) = ( x + 6 )/4
Step-by-step explanation:
f(x) is the same as...y = 4x + 6....and then try to make x the subject of formula
y + 6 = 4x
x = (y + 6)/4....then when writing f^-1(x)...replace y with x
f^-1(x) = ( x + 6 )/4